Peace without perfection: The intersections of realist and pacifist thought. (March 2018) - Moses, Jeremy
It is common in international relations thought to view realism and pacifism as lying at opposite ends of a spectrum on the permissibility of war. Pacifism, from this point of view, is necessarily antithetically opposed to and incompatible with realist thinking on the use of force. This article aims to counter this view and raise some critical questions concerning the incompatibilities of realism and pacifism through an examination of some points at which they may be seen to intersect. In pursuing these intersections, the first part of the article sets out the foundations of classical realist thought, focusing on the inherently conflictual depiction of human nature as the basis for a theory that insists upon the inescapable possibility of political violence. It then departs from the conventional narrative by setting out the intersections of pacifist and realist thought concerning the illogical and dangerous attempts to moralise war-fighting through the application of just war theory. Finally, it is proposed that a synthesis of some elements of pacifist and realist thought could lead to the development of new theories and strategies attuned to the promotion of non-violence in an inherently unstable and conflict-prone world.